Improving Motivation and Learning Outcomes Through the Application of the Student Facilitator and Explaining Model in the Al-Qur'an Hadits Subject at Elementary Islamic School - Suleman, Muh. Asharif; Febriansyah, Riza; Marliansyah, Anan; Hasanah, Ushie Uswatun; Nursholicha, Kurnia Utami; Idayanti, Zulfi (Universitas Pahlawan Tuanku Tambusai, 2024)
Increasing students' motivation and learning outcomes can be achieved through innovative and interactive learning methods. With this approach, students become more enthusiastic about learning and are able to achieve better results. A supportive learning environment and active involvement from teachers also play an important role in encouraging students to achieve their maximum potential. This study aims to improve the motivation and learning outcomes of the Al-Qur'an Hadith among students of MIN 1 Kendari through the application of the Student Facilitator and the Creating Learning Model. This study is classroom action research (CAR) carried out in two cycles on grade V students. The research procedure includes planning, implementation, observation, evaluation, and reflection. Data were collected through observation, tests, questionnaires, and documentation, then analyzed descriptively. The results of the study showed that: 1) The application of the student facilitator and the creating learning model can improve students' learning motivation at MIN 1 Kendari, as evidenced by the results of the learning motivation questionnaire reaching 88.88% in the very high category. 2) The application of this learning model can also improve students' learning outcomes, as indicated by the percentage of learning outcome completion of 81.48%